PERANCANGAN PENGUJIAN FUNGSIONAL DAN NON FUNGSIONAL APLIKASI SIAPPARA DI KABUPATEN HUMBANG HASUNDUTAN - Riyanthi Angrainy Sianturi; Arnaldo Marulitua Sinaga; Yohanssen Pratama; Hotni Simatupang; Julio Panjaitan; Sandy Sihotang (J-Icon : Jurnal Komputer dan Informatika, 2021)
SIAPPARA is an application that used to manage market retribution by Dinas Koperasi, Perdagangan Dan Industri kabupaten Humbang Hasundutan. The SIAPPARA application consists of two platforms, namely a web application used by the admin and treasurer and a mobile application used by market officers. The application has been used by market officers in 12 people's markets in Humbang Hasundutan. To ensure that all functions in the application have been running according to the design and requirements, it is necessary to test both functional and non functional features. Testing is carried out with the aim of finding failures in applications that have been used. Before testing the application, the researcher makes a test design including the selection of methods and stages of testing. The method used in this research is literature study and experiment. Researchers used the literature study method in collecting theoretical references and information related to functional and non functional testing of applications. Researchers use the experimental method to choose the test method to be used and make a test design for the method that has been selected.The results of this study is a design of testing activities using Category Based Partition testing method, the Usability Testing test method with the Heuristic Evaluation technique, and the Performance Testing method.